ANALISIS PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA LAYANAN JASA GOMED - Dini Dwi Ermawati; Angga Putri Ekanova (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of promotion and service quality partially and simultaneously on consumer satisfaction with gomed services. The data analysis methodin this study uses quantitative primary data obtained through distributing questionnaires to 100respondents who are students who use gomed services and live in the Bekasi City area. The samplingmethod in this research is purposive sampling, namely the technique of determining the sample withcertain considerations using the Non Probability sampling technique. The test stages carried out areValidity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test,Multiple Linear Regression Test, t Test (Partial), F Test (Simultaneous), and Coefficient ofDetermination Test (R2). The results of this study indicate that the promotion variable can partiallyand significantly affect consumer satisfaction on gofood services. The service quality variable canalso partially and significantly affect consumer satisfaction with gomed services. There is asimultaneous and significant influence between promotion and service quality on consumersatisfaction with gomed services.